Pulmonary Nontuberculous Mycobacterial Infection in Infants: A Systematic Review - Bai A; Belda O; Dosanjh A (Dove Medical Press, 2021)
Alice Bai,1 Olivia Belda,1 Amrita Dosanjh2 1Brown University, Providence, RI, USA; 2Pediatric Respiratory, Affiliated Staff Member, Department of Pediatrics, Rady Children's Hospital, San Diego, CA, USACorrespondence: Alice BaiBrown University, 69 Brown St. Mail# 5288, Providence, RI, 02912, USATel +1 770 843-2062Email alice_bai@brown.eduAbstract: Limited information and literature exist examining pulmonary infections caused by nontuberculous mycobacterial specifically in an infant population. The objective of our study was to summarize clinical characteristics and outcomes of infant patients with nontuberculous mycobacterial pulmonary infection via systematic literature review to identify common diagnostic and treatment regimens for this infection in infants. A search of MEDLINE and PubMed databases in October 2019 using MeSH search terms "infant," "NTM," "pulmonary," and "Mycobacterium abscessus" yielded 139 articles. Inclusion criteria were i) English-language studies including cases and case series with ii) established nontuberculous mycobacterial pulmonary infection in iii) a patient population of infants no older than 24 months. Patients with cystic fibrosis and any study which did not contain relevant information such as infection and age were excluded. This yielded data on 37 patients extracted from 28 studies analyzed. The most common strain was Mycobacterium avium complex, isolated in 56.8% of patient diagnoses. Bronchoscopy/thoracoscopy with a subsequent culture were the most common diagnostic techniques, utilized in 64.9% of cases. Drug therapeutic treatment was utilized in 86% of cases, with a median of three drugs administered. Notable limitations of this study are the small sample size and its retrospective nature, which relies on information reported in previous case studies. Although there is limited formal clinician consensus on the treatment of NTM pulmonary infection and how it may differ in an infant population, our findings indicate an informal consensus typically involving diagnostic lung specimen culture and antibiotic therapy.Keywords: nontuberculous mycobacterial, NTM, pulmonology, pediatrics